Heterocyclizations based on N-(R-hydrazine-1-carbonothioyl) cycloalkancarboxamides: functionalized azoles and their antimicrobial activity - Kholodniak, О. V.; Shubina, Yu. V.; Kovalenko, S. I.; Холодняк, Олена Валеріївна; Шубіна, Юлія Вікторівна; Коваленко, Сергій Іванович; Холодняк, Е. В.; Шубина, Ю. В.; Коваленко, С. И. (Запорізький державний медичний університет, 2022)
Aim. To investigate the heterocyclization of N-(R-hydrazine-1-carbonothioyl)cycloalkanecarboxa-mides, to establish the structure and antibacterial activity of the synthesized compounds. Materials and methods. Methods of organic synthesis, physical and physical-chemical methods of analysis of organic compounds (NMR 1H-spectroscopy, chromato-mass spectrometry, elemental analysis). The antimicrobial activity of the synthesized compounds was studied according to the generally accepted method for standard strains of microorganisms and fungi. Results. The peculiarities of heterocyclization of N-(R-hydrazine-1-carbonothioyl)cycloalkanecarboxamides have been studied and the factors influencing this reaction have been elucidated. It was shown that these compounds under the conditions of the heterocyclization reaction in concentrated mineral acids form 5-R-2-amino-1,3,4-thiadiazoles. The intermediate undergoes additional hydrolysis by cleavage of the cycloalkanecarboxyl fragment. Alternative methods for the synthesis of 5-R-2-amino-1,3,4-thiadiazoles were proposed. For the first time, the original 4-cycloalkanecarbonyl-3-(amino-,phenyloxo-(thio)methyl-1,5-dihydro-4H-1,2,4-triazole-5-thiones were synthesized by prolonged heating of the corresponding disubstituted thiosemicarbazides. It was not possible to extend this reaction to other diacylthiosemicarbazides, the latter undergo heterocyclization in the presence of sodium hydroxide with the formation of the known 5-R-2,4-dihydro-3H-1,2,4-triazole-3-thiones. 1H NMR spectra were studied, analyzed, and regularities of splitting of characteristic protons in functionalized azoles were established. Conducted microbiological screening was showed that 5-R-2-amino-1,3,4-thiadiazoles, 4-cycloalkanecarbonyl-3-(amino-,phenyloxo-(thio)methyl-1,5-dihydro- 4H-1,2,4-triazole-5-thiones and 5-R-2,4-dihydro-3H-1,2,4-triazole-3-thione were less effective antibacterial and antifungal agents (MIC 100–200 μg/ml) compared with N-(R-hydrazine-1-carbonothioyl)cycloalkanecarboxamides (MIC 3.125–200 μg/ml). Мета роботи – дослідити гетероциклізацію N-(R-гідразин-1-карбонотіоіл)циклоалканкарбоксамідів, встановити структуру та антибактеріальну активність синтезованих сполук. Матеріали та методи. Методики органічного синтезу, фізичні та фізико-хімічні методи аналізу органічних сполук (ЯМР 1Н-спектроскопія, хромато-мас-спектрометрія, елементний аналіз). Протимікробну активність синтезованих сполук досліджували згідно з загальноприйнятим методом до стандартних штамів мікроорганізмів і грибків. Результати. Дослідили особливості гетероциклізації N-(R-гідразин-1-карбонотіоіл)циклоалканкарбоксамідів і з’ясували фактори, що впливають на цю реакцію. Показано, що зазначені сполуки за умов реакції гетероциклізації в концентрованих мінеральних кислотах утворюють 5-R-2-аміно-1,3,4-тіадіазоли, тобто проміжний інтермедіат зазнає додаткового гідролізу з відщепленням циклоалканкарбоксильного фрагмента. Запропоновані альтернативні методи синтезу 5-R-2-аміно-1,3,4-тіадіазолів. Уперше синтезували оригінальні 4-циклоалканкарбоніл-3-(аміно-,фенілоксо-(тіо)метил-1,5-дигідро-4H-1,2,4-тріазол-5-тіони тривалим нагріванням відповідних дизаміщених тіосемикарбази- дів. Розширити цю реакцію на інші діацилтіосемікарбазиди не вдалося, останні зазнають гетероциклізації у присутності натрій гідроксиду з утворенням відомих 5-R-2,4-дигідро-3H-1,2,4-тріазол-3-тіонів. Досліджені та проаналізовані 1Н ЯМР-спектри, встановлені закономірності розщеплення характеристичних протонів у функціоналізованих азолів. Мікробіологічний скринінг показав, що 5-R-2-аміно-1,3,4-тіадіазоли, 4-циклоалканкарбоніл-3-(аміно-,фенілоксо-(тіо)метил-1,5-дигідро-4H-1,2,4-тріазол-5-тіони та 5-R-2,4-дигідро-3H-1,2,4-тріазол-3-тіон є менш ефективними антибактеріальними та протигрибковими агентами (MIC 100–200 мкг/мл) порівняно з N-(R-гідразин-1-карбонотіоіл) циклоалканкарбоксамідами (MIC 3.125–200 мкг/мл). Цель работы – исследовать гетероциклизацию N-(R-гидразин-1-карбонотиоил)циклоалканкарбоксамидов, установить структуру и антибактериальную активность синтезируемых соединений. Материалы и методы. Методики органического синтеза, физические и физико-химические методы анализа органических соединений (ЯМР 1Н-спектроскопия, хромато-масс-спектрометрия, элементный анализ). Противомикробную активность синтезированных соединений исследовали согласно общепринятому методу к стандартным штаммам микроорганизмов и грибков. Результаты. Исследованы особенности гетероциклизации N-(R-гидразин-1-карбонотиоил)циклоалканкарбоксамидов и выяснены факторы, влияющие на данную реакцию. Показано, что указанные соединения при реакции гетероциклизации в концентрированных минеральных кислотах образуют 5-R-2-амино-1,3,4-тиадиазолы, то есть промежуточный интермедиат подвергается дополнительному гидролизу с отщеплением циклоалканкарбоксильного фрагмента. Предложены альтернативные методы синтеза 5-R-2-амино-1,3,4-тиадиазолов. Впервые синтезированы оригинальные 4-циклоалканкарбонил-3-(амино-,фенилоксо-(тио)метил-1,5-дигидро-4H-1,2,4-триазол-5-тионы продолжительным нагреванием соответствующих дизамещённых тиосемикарбазидов. Расширить данную реакцию на другие диацилтиосемикарбазиды не удалось, последние подвергаются гетероциклизации в присутствии гидроксида натрия с образованием известных 5-R-2,4-дигидро-3H-1,2,4-триазол-3-тионов. Исследованы и проанализированы 1Н ЯМР-спектры, установлены закономерности расщепления характеристических протонов у функционализированных азолов. Проведённый микробиологический скрининг показал, что 5-R-2-амино-1,3,4-тиадиазолы, 4-циклоалканкарбонил-3-(амино-,фенилоксо-(тио)метил-1,5-дигидро-4H-1,2,4-триазол-5-тионы и 5-R-2,4-дигидро-3H-1,2,4-триазол-3-тион являются менее эффективными антибактериальными и противогрибковыми агентами (MIC 100–200 мкг/мл) по сравнению с N-(R-гидразин-1-карбонотиоил)циклоалканкарбоксамидами (MIC 3.125–200 мкг/мл).
Гетероциклізація на основі N-(R-гідразин-1-карбонотіоіл)циклоалканкарбоксамідів: функціоналізовані азоли та їхня протимікробна активність
Гетероциклизация на основе N-(R-гидразин-1-карбонотиоил)циклоалканкарбоксамидов: функционализированные азолы и их противомикробная активность
Kholodniak O. V. - ORCID ID: 0000-0002-0518-4262; Shubina Yu. V. -ORCID ID: 0000-0002-7751-4769; Kovalenko S. I. - ORCID ID: 0000-0001-8017-9108.
Keywords: N-(acylhydrazine-1-carbonothioyl)cycloalkanecarboxamides; heterocyclization; 1,3,4-thiadiazoles; 1,2,4-triazoles; antimicrobial activity; N-(ацилгідразин-1-карбонотіоіл)циклоалкан-карбоксаміди; гетероциклізація; 1,3,4-тіадіазоли; 1,2,4-тріазоли; протимікробна активність; N-(ацилгидразин-1-карбонотиоил)циклоалканкарбоксамиды; гетероциклизация; 1,3,4-тиадиазолы; 1,2,4-триазолы; противомикробная активность